Employment impact of electronic business. - Hecker, Daniel E. (Monthly Labor Review, 2001)
E-business, consisting of marketing and other business processes, is changing the way organizations in many industries function. It results in the automation of some job functions and replaces others with self-service operations, boosting output per worker and dampening employment requirements in some occupations, as well as in the industries in which those occupations are concentrated. It has also spurred employment in industries producing hardware, software, and systems used by e-businesses and in computer and other occupations associated with Web sites and networks. The writer discusses whether e-business will stimulate or dampen employment or output in a number of industries and occupations.